Concurrent and Convergent Validity of Goniometers Versus Bubble Inclinometers in Measuring Thoracolumbar Movement in Low Back Pain Patients - Novita Intan Arovah; Irena Agustiningtyas; Karina Satyani Pratiwi (Rehabilitacja Medyczna)
Background: Low back pain (LBP) can impair mobility by limiting thoracolumbar range of motion (ROM). Goniometers and inclinometers are commonly used for assessing ROM, with inclinometers theoretically offering better accuracy and usability than traditional goniometers.Objective: The concurrent and convergent validity of standard goniometers and bubble inclinometers in measuring thoracolumbar ROM in LBP patients was assessed in this study.Material and Methods: A cross-sectional study involving 45 non-specific LBP patients was conducted. Goniometers and bubble inclinometers were used to assess ROM across movements, including flexion, extension, lateral flexion and rotation of each patient. Pain and thoracolumbar function were assessed using the Visual Analog Scale (VAS) and the Oswestry Disability Index (ODI). Concurrent validity was evaluated by intraclass correlation and assessment with Bland-Altman plotting of the differences, while convergent validity was examined via Spearman correlation analysis between ROM and both pain and function.Results: Both tools showed substantial agreement, with ICCs ranging from 0.78 to 0.88, and the Bland-Altman plots indicating good agreement with a few outliers, while negative correlations between ROM and VAS or ODI scores, thus, demonstrating strong convergent validity of both tools.Conclusion: Both goniometers and bubble inclinometers are recommended for measuring ROM among LBP. Thus, despite inclinometers being perceived as more accurate, goniometers maintain relevance in clinical settings.